2019
DOI: 10.1007/978-1-4939-9546-2_15
|View full text |Cite
|
Sign up to set email alerts
|

BioID as a Tool for Protein-Proximity Labeling in Living Cells

Abstract: BioID has become an increasingly utilized tool for identifying candidate protein-protein interactions (PPIs) in living cells. This method utilizes a promiscuous biotin ligase, called BioID, fused to a protein-of-interest that when expressed in cells can be induced to biotinylate interacting and proximate proteins over a period of hours, thus generating a history of protein associations. These biotinylated proteins are subsequently purified and identified via mass spectrometry. Compared to other conventional me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 35 publications
4
83
0
Order By: Relevance
“…Numerous proteinprotein interactions guiding the folding, modifications, and trafficking of the secreted and membrane proteins through the secretory pathway are transient 50,51 and therefore cannot be captured by the conventional methods such as co-immunoprecipitation. Consistent with the previous studies 52 , these results showed the BioID can detect weak and transient interactions in situ. This is important since numerous interactions in the secretory pathway are transient (e.g., chaperones aiding folding or enzymes adding PTMs).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Numerous proteinprotein interactions guiding the folding, modifications, and trafficking of the secreted and membrane proteins through the secretory pathway are transient 50,51 and therefore cannot be captured by the conventional methods such as co-immunoprecipitation. Consistent with the previous studies 52 , these results showed the BioID can detect weak and transient interactions in situ. This is important since numerous interactions in the secretory pathway are transient (e.g., chaperones aiding folding or enzymes adding PTMs).…”
Section: Discussionsupporting
confidence: 92%
“…BioID2 requires less biotin supplementation, and exhibits enhanced labeling of proximate protein 20 . BioID2 was shown to improve localization and was more sensitive to a lower biotin concentration, potentially allowing for BioID to be introduced to new systems where biotinylation supplementation may not be easily accomplished 52 . More recently, Ting's group has developed two promiscuous mutants of biotin ligase, TurboID and miniTurbo, which catalyze proximity labeling even with much greater efficiency 54 .…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in the introduction, this in situ covalent labeling allows for lysis of cells under harsh conditions to maximize protein solubility without the need for preserving protein interactions or subcellular organization. The biotinylated proteins can then be captured on streptavidin-conjugated resin (or alternatively through anti-biotin antibodies; see below) and identified by mass spectrometry (19,52,54) or detected through different means, such as immunoblotting (Figure 1). by guest on July 8, 2020 https://www.mcponline.org…”
Section: Downloaded Frommentioning
confidence: 99%
“…Studying the interactions of proteins aids in the understanding of their cellular roles under normal and stress conditions. Co-immunoprecipitation, crosslinking, and BioID are some techniques used to identify interacting proteins (Lin and Lai, 2017;Yu and Huang, 2018;Sears et al, 2019). GCE can be used to insert crosslinking ncAAs at known or potential binding interfaces to increase the chances of identifying interacting proteins as well as minimize interference with protein folding and activity.…”
Section: Identifying Protein-protein Interactionsmentioning
confidence: 99%